(untitled) (Bangladesh Journal of Animal Science, 2022)
The experiment was carried out to investigate the effects of neem (Azadirachta indica) leaf powder (NLP) over a period of 35 days on the growth performance, dressing parameters, serum biochemical parameters and profitability of broiler meat. Day old broiler chicks (n = 320) were randomly assigned to five dietary groups, each with four replicates. The dietary treatment groups were; control (basal diet; no additives), antibiotic (basal diet + antibiotic), NLP 0.25% (basal diet + 0.25% NLP), NLP 0.375% (basal diet + 0.375% NLP) and NLP 0.50% (basal diet + 0.50% NLP). Results showed that the body weight, body weight gain, feed intake and FCR were differed significantly (P<0.05) among the treatment groups. Body weight and body weight gain were higher in antibiotic, NLP 0.25% and NLP 0.375% group compare to the NLP 0.50% group. Total feed intake was not different significantly (P>0.05). Better (P<0.05) FCR was observed in NLP 0.25% group as such as antibiotic group compare to the control and NLP 0.50% group. The results also showed that dressing parameters were not significantly (P>0.05) different among the dietary groups. Serum glucose, triglyceride, GOT, GPT and cholesterol level were non-significant (P>0.05) among the dietary groups. However, HDL was significantly (P<0.05) higher in NLP 0.25% group compared to the control group. Higher profitability was found in NLP-0.25% group and antibiotic group when all the birds were sold at market price. It can be concluded that the addition of NLP to broiler diet had a positive effect on growth performances but no negative effect on dressing parameters and serum biochemical parameters. Moreover, NLP at the level of 0.25% increases HDL level and improve profitability. It can be suggested that neem leaf powder up to 0.375% could be potential feed additive in broiler diet. Bang. J. Anim. Sci. 2021. 50 (2): 114-122